In Vitro and in Silico Evaluation of Allium sativum Extract as an Antimicrobial Strategy against Cariogenic Bacteria - Jasim, Haider Mahmod; Mohammed, Shams Kareem; Jasim, Zaid Mohammed; Kamarudin, Nurshanariah Balkis (American Journal of Biology and Natural Sciences, 2026)
Dental caries is a complex oral disorder resulting from the interaction of multiple contributing factors, with microbial activity playing a central role. It continues to represent a significant global health burden. The rising incidence of antibiotic resistance among cariogenic microorganisms has diminished the efficacy of traditional antimicrobial treatments, thereby emphasizing the urgent need for alternative therapeutic approaches. Molecular characterization of bacterial isolates was achieved through PCR amplification of species-specific gene sequences. The antibiotic sensitivity profile was determined using the standard Kirby–Bauer disk diffusion assay. Furthermore, the antimicrobial potential of garlic extract was investigated and evaluated in comparison with commonly utilized antibiotics. Molecular docking analysis was carried out using allicin, the principal bioactive compound of garlic, against essential bacterial enzymes, including DNA gyrase and topoisomerase, to elucidate protein–ligand interactions. The results revealed a polymicrobial profile of dental caries, with Streptococcus mutans and Lactobacillus acidophilus being the most prevalent species, followed by Porphyromonas gingivalis and Staphylococcus aureus. Antibiotic susceptibility testing demonstrated considerable resistance to amoxicillin, ampicillin, and erythromycin, whereas garlic extract exhibited notable antibacterial activity against most isolates. Molecular docking results showed strong binding affinities of allicin toward DNA gyrase and topoisomerase, supported by stable hydrogen bonding and hydrophobic interactions. In conclusion, the integration of molecular diagnostics, in vitro antimicrobial evaluation, and in silico analysis provides valuable insight into alternative strategies for managing dental caries and addressing antimicrobial resistance.